The Spectrum of Care: Integrative Multidisciplinary Approaches to Healthcare Innovation - Mufeed Mohammed Almuhanna, Mohammed Suliman Saleh Alhumaid, Abdulrahman Alamat Al-Anazi, Nader Moayed Farhan Al-Anazi, Mohammed Nasser Almaklifi, Reem Zafer Alshehri, Abdulaziz Hamad Abdulwahab Alabdulwahb,; Jawaher Madhkar Al-Shalawi, Mohammed Fahad Almukhlifi, Khalid Abdulrahman Sulaiman Alhumaied, Matog Fadhel Maqbul, (International Journal of Medical Toxicology and Legal Medicine, 2024)
The healthcare landscape is evolving, with integrative multidisciplinary approaches becoming increasingly critical in delivering holistic and patient-centered care. This paper explores the concept of the spectrum of care, emphasizing how collaboration across various healthcare disciplines leads to innovative practices that address the diverse needs of patients. Integrative care models blend conventional and complementary therapies, leveraging technological advancements and continuous feedback mechanisms to optimize patient outcomes. This manuscript discusses the key components, challenges, and opportunities associated with these approaches, underscoring the transformative potential they hold for improving healthcare delivery and patient well-being.